Evaluation of Salt Influence on Sugar Consumption by Suspension Cells Based on Spectroscopic Analysis - Suehara, Ken-ichiro; Kameoka, Takaharu; Hashimoto, Atsushi (Journal of Analytical Methods in Chemistry, 2013)
The influence of metal salt on sugar consumption by suspension cells in food models constructed by a sugar and salt aqueous solution was investigated based on mid-infrared spectroscopic analysis. The contaminated suspension cells in the food model could be detected using the spectral feature change that measured the present spectrum subtracted in the initial spectrum. The cells were prepared for growth and although the cell did not grow under the induction period, the cell activation (start of sugar metabolism) was detected on the subtracted spectral behavior before the cell growth. The rough grasp of the spectral change behavior is useful for the high-throughput spectroscopic method to detect the contaminated cell activation. Furthermore, the detailed sugar consumption kinetics of the cells was also investigated based on the spectroscopic method. The kind of added salt in the food model influenced the cell activation and the potassium ions play an important role in the plant cells. The living cells activity in fresh food may act to prevent microbial contamination and to suppress the growth of the contaminated microorganism. Both the simple and detailed analyses based on the spectroscopic method presented in this study might be useful for risk management of food.